Lectotypifications in Oxalis (Oxalidaceae) for the Flora of Argentina - López, Alicia; Sassone, Agostina B.; Fiaschi, Pedro (Phytotaxa, 2018)
As part of a revision of Oxalis for the Flora Argentina, the types of all the relevant names for the country were assessed. Seven names were inadvertently lectotypified before 2001, but require second-step lectotypifications. As a whole, eleven lectotypes (first and second step) are designated here.